Operation and development of electronic markets as prognostic instrument for business planning - Schieg, Martin (Journal of Business Economics and Management, 2005)
Strategic planning is crucial for the survival of a company, wide‐ranging decisions about future action must be taken. The information basis for such decisions is often gained from forecasts about the future with more or less accurate probability of the assumed event occurring. Electronic markets have been the subject matter of numerous investigations in recent years and if organized correctly show a high degree of accuracy in forecasting future events relevant to the business of a company. In major enterprises prediction markets have already been used successfully as a new kind of prognostic instrument. It is also suitable, however, for small and medium‐sized enterprises for the gathering and assessment of the information available to the employees. When developing prognostic markets it is necessary to take into consideration psychological factors, which could favour incorrect results.First published online: 14 Oct 2010